Analisis Faktor-Faktor yang Berperan dalam Kualitas Tidur pada Mahasiswa Tingkat Akhir - Dina Mariana Siregar; Chrystilia Afiyah Rengkuan (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
This study aims to analyze the factors that influence the sleep quality of final year students, focusing on the role of stress, anxiety, physical activity and parental support. Final year students often deal with high levels of academic pressure, such as writing a thesis, which can disrupt their sleep patterns. This research uses a qualitative descriptive approach with literature study to identify the main themes related to students' sleep quality. Findings suggest that high levels of stress and anxiety, especially related to academic deadlines, negatively impact sleep quality. Apart from that, intense physical activity and lack of social support from parents also contribute to sleep disorders. The implications of this research demonstrate the importance of managing stress and anxiety, as well as the need for emotional and practical support to help students maintain the quality of their sleep. This research provides insights for universities to design programs that support student well-being, as well as contributing to research related to final year student mental health and sleep.